Love me, love me not. Vol. 3 - Sakisaka, Io; Thistlethwaite, Nancy (Shojo beat manga., 2021)
"Love and friendship have become quite complicated for these four friends. Akari finds herself attracted to Kazuomi even though he's very different from her usual type, but he seems completely uninterested in love. When Rio learns that Akari likes Kazuomi, his state of mind makes Yuna's heart ache."--Back cover.